Decreased interlimb differences in female basketball players - Akpinar, S. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: Hand preference can be influenced by some factors like sensory information and sports participation. In many sports, it is always desirable to have the similar performance of both hands to adapt to the fast changes of the game. Elite basketball players use their left non-dominant hand more accurately and more frequently during the game compared to amateurs. However, there is no quantitative data to explain this phenomenon. The aim of the study was to test whether participation of long-term basketball training influences interlimb difference and also observed more accurate and more frequent usage of the non-dominant hand in basketball players that can be explained by some kinematic variables during an aiming task.